Character building in the novel (Ajwan) by Noura Al Nouman: A critical study - Alteneiji, Moza; Darabseh, Mahmoud (Al-Adab Journal, 2024)
Science fiction literature in the developed world claims great interest in literary and critical circles. It is not possible to research science fiction novels in the Emirates without the name of the writer Nora Ahmed Al-Noman, who is considered the first Emirati writer and novelist specializing in the field of science fiction. Through this research, we shed light on the first Emirati female novelist who wrote a science fiction novel in her novel (Ajwan). Science fiction is the best way to link literary culture with scientific culture, and it is a kind of fantasy that takes the reality of scientific and technological progress on society and individuals as its main theme. The novelist Noura Al-Noman believes that the fantasy novel, as it is called in the West, “Fantasia”, includes fairy tales and wonders, in which events are characterized by strangeness and cannot be realized and this cannot be explained scientifically, an example of which is the famous “Harry Potter” novels. Whereas, a science fiction novel or story considers everything that is strange, impossible, or absurd that it could happen if science developed. The personality is one of the most important components on which the artwork is based, as it is an important element in every narrative, as there is no novel without a character who leads the events and organizes the actions. The personality has a prominent role in activating the events. In a science fiction novel, we will not be in front of characters with familiar physiological dimensions, but rather we will be in front of a new human composition, as the temporal and spatial contrast calls for a different personality.